Optimising 3D-printed flexible lattice structures for morphing applications by linking rheology to mechanical behaviour - Laia Farràs-Tasias; Max Vermeerbergen; Francisco A. Gilabert; Ludwig Cardon; Flavio H. Marchesini (Virtual and Physical Prototyping)
Additive manufacturing, particularly extrusion-based additive manufacturing (EB-AM), has transformed the fabrication of complex structures. Thermoplastic Polyurethane (TPU), valued for its elasticity and durability, is an ideal material for flexible lattice designs. However, determining optimal rheological properties and printing parameters during extrusion remains a significant challenge. This study introduces the 3DFLOR framework (3D Flexible Lattice Optimisation via Rheology), a novel methodology that combines the Doehlert experimental design and Response Surface Methodology (RSM) to minimise trial and error in EB-AM. By systematically adjusting critical printing parameters, such as printing temperature and speed, the 3DFLOR framework establishes a link between the rheological and the mechanical properties. The experimental results show an enhancement of the mechanical properties tailored for the morphing application. This research not only provides a specific application optimisation but a universal methodology for optimising and linking rheology and material properties in other applications.